2015
DOI: 10.1016/j.celrep.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

KDEL Receptors Assist Dengue Virus Exit from the Endoplasmic Reticulum

Abstract: Membrane receptors at the surface of target cells are key host factors for virion entry; however, it is unknown whether trafficking and secretion of progeny virus requires host intracellular receptors. In this study, we demonstrate that dengue virus (DENV) interacts with KDEL receptors (KDELR), which cycle between the ER and Golgi apparatus, for vesicular transport from ER to Golgi. Depletion of KDELR by siRNA reduced egress of both DENV progeny and recombinant subviral particles (RSPs). Coimmunoprecipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 43 publications
3
43
2
4
Order By: Relevance
“…Using RSPs, we demonstrated that sequestering KDELR in Golgi apparatus by depletion of the small GTPases Arf4 and Arf5 accumulated RSPs in the ER [7]. We have now found that KDELR knockdown by siRNA reduced egress of RSPs and DENV and have identified three positive charged amino acid residues at the N-terminus of prM that mediate interaction with KDELR in vitro [5]. Only KDELR1 and 2 were involved, similarly to what observed for ECM degradation [4].…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Using RSPs, we demonstrated that sequestering KDELR in Golgi apparatus by depletion of the small GTPases Arf4 and Arf5 accumulated RSPs in the ER [7]. We have now found that KDELR knockdown by siRNA reduced egress of RSPs and DENV and have identified three positive charged amino acid residues at the N-terminus of prM that mediate interaction with KDELR in vitro [5]. Only KDELR1 and 2 were involved, similarly to what observed for ECM degradation [4].…”
mentioning
confidence: 82%
“…These findings place KDLER at the center of a complex system of signals, which originate at the Golgi but exert their effects at multiple levels. Two recent papers have shed new light on the role of KDELR by implicating them in as diverse functions as cell invasion [4] and virus infection [5]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To address mechanisms of virus release, we previously established a cell-line that stably expresses the Dengue structural proteins pre-membrane (prM) and envelope (E), and constitutively secretes non-infectious recombinant virus like particles (VLPs) 13,14 . Transport of these VLPs mimic the intracellular trafficking characteristics of infectious Dengue particles -thus providing a convenient method to identify the molecular determinants of Dengue secretion without confounding effects from viral entry and replication.…”
Section: Introductionmentioning
confidence: 99%
“…Transport of these VLPs mimic the intracellular trafficking characteristics of infectious Dengue particles -thus providing a convenient method to identify the molecular determinants of Dengue secretion without confounding effects from viral entry and replication. Using this tool, we determined that interaction between Dengue prM and cellular KDEL receptors (KDELRs) facilitated ER-to-Golgi transport of newly formed Dengue particles 13 .…”
Section: Introductionmentioning
confidence: 99%